Effects of Core Antigen Bacterin with an Immunostimulant on Piglet Health and Performance Outcomes When Challenged with Enteric and Respiratory Pathogens - Charley A. Cull; Vijay K. Singu; Jenna J. Bromm; Kelly F. Lechtenberg; Raghavendra G. Amachawadi; Brooke J. Cull (MDPI AG, 2023)
A total of 90 pigs, approximately one day of age, were used in a 42-day study to evaluate whether Endovac-Porci, a core antigen vaccine with an immunostimulant, provides piglets with broad-spectrum protection against the enteric and respiratory effects of Gram-negative bacteria. This study was a single-site, randomized, prospective, blinded, comparative placebo-controlled design. Individual pigs were randomly allocated to 1 of 2 treatments in a randomized design. An individual pig was considered the experimental unit for the farrowing phase (Study day 0 to 21), and the pen was considered the experimental unit for the nursery phase (Study day 21 to 42). Thus, there were 45 replications per treatment during the farrowing phase and 15 replications per treatment during the nursery phase. Treatments included a control product (saline; CP) and an investigational product (Endovac-Porci; IVP). On Study day 23, all pigs were challenged with enterotoxigenic Escherichia coli strain expressing K88 (F4) fimbriae and Pasteurella multocida. Individual pigs were weighed and feed consumption was measured to determine body weight gain, average daily gain, and feed-to-gain ratio. Clinical and fecal scores and overall health were recorded daily. Overall, administering the IVP to pigs led to an increase (p < 0.01) in body weight gain and average daily gain compared to pigs administered the CP. Pigs administered the IVP had reduced (p < 0.01) mortality compared to pigs administered the CP. There was a Study day × treatment interaction on clinical and fecal scores (p < 0.01). There was also a main effect of Study day where clinical and fecal scores increased (p < 0.01) as the Study day increased. Treatment also had an effect on clinical and fecal scores, where pigs administered the IVP had lower (p < 0.01) clinical and fecal scores compared to pigs administered the CP. In conclusion, administering pigs with the Endovac-Porci vaccination significantly improved the performance (i.e., body weight, body weight gain, and average daily gain) and health (i.e., clinical and fecal scores), while reducing the overall mortality in pigs challenged with E. coli K88 orally and Pasteurella multocida intranasally post-weaning. Results from this study suggest that Endovac-Porci could provide broad-spectrum protection against enteric and respiratory effects of Gram-negative bacteria in piglets.